Per- and polyfluoroalkyl substances (PFASs) in Chinese and German river water samples collected in 2018 - Hanna Joerss; Thekla-Regine Schramm; Linting Sun; Chao Guo; Jianhui Tang; Ralf Ebinghaus (PANGAEA, 2021)
Legacy and emerging per- and polyfluoroalkyl substances (PFASs) were measured in Chinese and German river water samples affected by industrial point sources. In China, sites located at the Yangtze River, at the Xi River and in the Xiaoqing River Basin were selected. In Germany, the selected sites were situated at the Rhine River, Ruhr River, Main River and Alz River. Samples were collected from up- and downstream of seven suspected point sources in autumn 2018. Solid-phase extraction was used for sample preparation before instrumental analysis was performed by liquid chromatography coupled to a triple quadrupole mass spectrometer (LC-MS/MS). More information can be found in https://doi.org/10.1016/j.envpol.2020.115567. The study aimed at comparing source-specific fingerprints of PFASs in river water from China and Germany, selected as countries with different histories of PFAS production.